2021
DOI: 10.1186/s42269-020-00459-w
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of ten rice brands to weevil, Sitophilus oryzae L. (Coleoptera: Curculionidae), and their influence on the insect and infestation rate

Abstract: Background Susceptibility studies keep farmers, managers and household users informed and enhance breeding program’s testing against infestation and damage by storage insect pests. Therefore, laboratory tests were carried out to examine the susceptibility of ten rice brands to rice weevil, Sitophilus oryzae L. (Coleoptera: Curculionidae), infestation under temperature and relative humidity of 25 ± 2 °C and 75 ± 5%, respectively. The specific objectives of the study were to identify some commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…In this study, the marked differences observed on the mortality of S. oryzae on treated and untreated polished rice grains (Table 2) indicate that all the plant oil extracts used in the experiment exerted remarkable effects on the mortality of the rice weevils. This result is consistent with the report that plant extracts often consist of complex mixtures of bioactive constituents which may produce toxic effects [3,42,44] . It is deduced from the present study that the effectiveness of these oils could be due to their toxicity which caused blocking of the insect's specimen spiracles and as a result hindered their movements in the treated containers.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the marked differences observed on the mortality of S. oryzae on treated and untreated polished rice grains (Table 2) indicate that all the plant oil extracts used in the experiment exerted remarkable effects on the mortality of the rice weevils. This result is consistent with the report that plant extracts often consist of complex mixtures of bioactive constituents which may produce toxic effects [3,42,44] . It is deduced from the present study that the effectiveness of these oils could be due to their toxicity which caused blocking of the insect's specimen spiracles and as a result hindered their movements in the treated containers.…”
Section: Discussionsupporting
confidence: 93%
“…The percentage of rice weight loss depends on the length of time the rice is infested by S. oryzae. According to Okpile et al, [47], so far no rice is resistant to S. oryzae. This is based on the results of his research, that of the 10 types of rice (royale stallion, mama royale, parboiled rice, mama gold, white rice, super eagle, indian rice, champion rice, abakiliki rice, and mama africa) none of them are resistant and permanent, experienced weight loss with an average of 19%.…”
Section: Discussionmentioning
confidence: 99%
“…Its capacity to infest a variety of grains amplifies the economic losses associated with stored grain pests, making S. oryzae a crucial target for effective pest management strategies (Togola et al, 2013;Yaseen et al, 2019). The economic impact of S. oryzae infestation underscores the urgency to develop sustainable and targeted solutions to mitigate its detrimental effects on stored grains (Togola et al, 2013;Buffon et al, 2018;Derbalah et al, 2021;Okpile et al, 2021;Cao et al, 2024). S. oryzae exhibits remarkable versatility in targeting a broad spectrum of grains, including wheat, rice, and barley Okpile et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The economic impact of S. oryzae infestation underscores the urgency to develop sustainable and targeted solutions to mitigate its detrimental effects on stored grains (Togola et al, 2013;Buffon et al, 2018;Derbalah et al, 2021;Okpile et al, 2021;Cao et al, 2024). S. oryzae exhibits remarkable versatility in targeting a broad spectrum of grains, including wheat, rice, and barley Okpile et al, 2021). Its adaptability to infest diverse grains throughout the supply chain poses a significant threat to global food reserves, contributing to the challenge of preserving stored grains and exacerbating economic losses (Choudhury and Chakraborty, 2014;Zunjare et al, 2015;Derbalah et al, 2021;Kanmani et al, 2021;Kanyile et al, 2023;Mohammad et al, 2023;Cao et al, 2024).…”
Section: Introductionmentioning
confidence: 99%